Effect of Diet Supplemented With Rapeseed Meal or Hydrolysable Tannins on the Growth, Nutrition, and Intestinal Microbiota in Grass Carp (Ctenopharyngodon idellus) - Yao, Jingting; Chen, Peng; Ringø, Einar; Zhang, Gaigai; Huang, Zhongyuan; Hua, Xueming (Frontiers in Nutrition, 2019)
Grass carp (Ctenopharyngodon idellus; n = 320) were received four different diets for 56 days. The experimental diets were: fishmeal (FM) containing 10% fishmeal (without rapeseed meal), and rapeseed meal (RM) containing 50% rapeseed meal (without fishmeal), and two semi-purified diets either without (T0) or with 1.25% (T1) supplemental hydrolysable tannin. The approximate content of tannin in the RM diet was 1.31%, which was close to that of T1, while the tannin content of FM was close to that of T0. The weight gain rate of grass carp of the RM group was significantly lower than that of the FM group, while the feeding conversion ratio and the feeding rate were significantly higher in the T1 group than in T0. The muscle lipid content was significantly lower in RM than in FM, while T1 was lower than T0. Intestinal activities of trypsin and α-amylase were significantly higher in T1 and RM groups compared with the other treatments. The hepatic activities of aspartate aminotransferase and alanine aminotransferase were lower in T1 and RM groups compared with the other treatments, while hepatic glycogen and malonaldehyde were significantly higher in T1 and RM groups. In serum, the total protein and globulin contents were significantly higher in T1 and RM groups, while albumin was significantly lower in the RM group compared to the FM group. High-throughput sequencing showed that Proteobacteria, Firmicutes, and Actinobacteria were the dominant bacterial phyla among groups. The intestinal microbial diversity was higher in T1 and RM. Redundancy analysis showed that tannin, rapeseed meal, and intestinal trypsin activity were positively or negatively correlated with the relative abundance of several different intestinal microbiota at phylum and/or genus levels. The results indicated that 1.25% tannin could not be the main reason for the poor growth of grass carp of the RM group; however, the protein metabolism was disturbed, the absorption of carbohydrate was improved, and the accumulation of lipid had decreased. Furthermore, tannin and rapeseed meal supplementations modulated the intestinal microbiota, and may sequentially regulate the intestinal function by fermenting dietary nutrition, producing digestive enzymes, and modulating probiotics.